Manajemen Kinerja Pegawai Dinas Pendidikan dan Kebudayaan Kabupaten Tanah Datar - Khairunnisah Lbs; Sufyarma Marsidin (Universitas Negeri Padang, 2019)
This research was based on the observation of the author at the Tanah Datar District Education and Culture Office conducted by the leadership, namely the Head of the Division and the Head of the Session which were categorized Good. This type of research is descriptive research. The population of this study was all employees at the Tanah Datar District Education and Culture Office, which numbered 62 people. The data collection tool in this study is a questionnaire or questionnaire, which is arranged in the form of a Likert sketch that has been tested for validity and reliability. Data analyzed using the average formula. The results showed that the performance management of employees at the Tanah Datar District Education and Culture Office showed that 1) employee performance planning was in the Good category with an average score of 3.75, 2) the implementation of employee performance is in the Good category with an average score of 3.73, 3) the assessment of employee performance is in the category of Good Enough with an average score of 3.58, 4) reviewing employee performance in the Good category, with an average score of 3.67, 5) improvement in employee performance in the Good category with an average score namely 3.63, and then general the performance management of the Culture and Education Office of the Tanah Datar District staff has been well managed.